Fasciclin-Like Arabinogalactan-Protein 16 (FLA16) Is Required for Stem Development in Arabidopsis - Liu, Edgar; MacMillan, Colleen P.; Shafee, Thomas; Ma, Yingxuan; Ratcliffe, Julian; van de Meene, Allison; Bacic, Antony; Humphries, John; Johnson, Kim L. (Frontiers in Plant Science, 2020)
The predominant Fascilin 1 (FAS1)-containing proteins in plants belong to the Fasciclin-Like Arabinogalactan-protein (FLA) family of extracellular glycoproteins. In addition to FAS1 domains, these multi-domain FLA proteins contain glycomotif regions predicted to direct addition of large arabinogalactan (AG) glycans and many contain signal sequences for addition of a glycosylphosphatidylinositol (GPI)-anchor to tether them to the plasma membrane. FLAs are proposed to play both structural and signaling functions by forming a range of interactions in the plant extracellular matrix, similar to FAS1-containing proteins in animals. FLA group B members contain two FAS1 domains and are not predicted to be GPI-anchored. None of the group B members have been functionally characterized or their sub-cellular location resolved, limiting understanding of their function. We investigated the group B FLA16 in Arabidopsis that is predominantly expressed in inflorescence tissues. FLA16 is the most highly expressed FLA in the stem after Group A members FLA11 and FLA12 that are stem specific. A FLA16-YFP fusion protein driven by the endogenous putative FLA16 promoter in wild type background showed expression in cells with secondary cell walls, and FLA16 displayed characteristics of cell wall glycoproteins with moderate glycosylation. Investigation of a fla16 mutant showed loss of FLA16 leads to reduced stem length and altered biomechanical properties, likely as a result of reduced levels of cellulose. Immuno-labeling indicated support for FLA16 location to the plasma-membrane and (apoplastic) cell wall of interfascicular stem fiber cells. Together these results indicate FLA16, a two-FAS1 domain FLAs, plays a role in plant secondary cell wall synthesis and function.